Bird migration a new understanding - Rappole, John H. (Johns Hopkins University Press, 2022)
"The author summarizes and translates the scientific data behind avian migration into everyday language. New technologies, such as molecular genetics, global positioning systems, and transmitter miniaturization, have revealed fresh insights into the behavior and movement of birds that have overturned much of the received scientific wisdom about bird migration"--Provided by publisher